Are black pepper and white pepper markets co-integrateda non-parametric approach - Habibullah, Muzafar Shah; Baharumshah, Ahmad Zubaidi (Universiti Putra Malaysia, 1994)
The objective of this study is to determine the linkages between Black Pepper and White Pepper markets in Malaysia. For a spatially integrated market, two products are considered to compete in the same market. Using a sample of 138 monthly data on Black Pepper and White Pepper prices series for the period January 1981 to June 1992, our co-integration analysis suggest that Black Pepper and White Pepper markets in Malaysia are not co-integrated.